Embodiment of Ukrainian folk elements in Valerii Ivko’s «Shchedrivka» - Diakova, Anastasiia (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2024)
The relevance of the study is determined by the need for an in-depth analysis of the features of Valerii Ivko’s performance style, in particular in the context of the folklore fairway of his works. Main objective of the study is highlight folklore motifs in the original domra composition, reveal their archaic origins and enrich ideas about Valerii Ivko’s compositional style. The methodology includes method of structure analysis to identify the main stylistic Valerii Ivko’s techniques and method of comparative analysis is used to study the connection between the archaic and the modern musical embodiment, as well as in the study of folklore elements of the work and the influence of the ancient environment on the human worldview. Results and conclusions. The historical and geographical context of the formation of the genre of charity was established, thereby clarifying the cultural basis of Valerii Ivko’s creative idea. "Schedrivka" for domra and piano is a bright and virtuosic work that faithfully reflects the author’s musical style. The composer successfully combined several types of techniques of working with folklore material, including citation, variation of the musical text, and author’s reworking with features of polyphony. The following features of the approach to the composer’s interpretation of the genre of generosity were noted: enrichment of the theme with achievements of classical means of composition, such as modern methods of harmony, texture; shading of the main theme thanks to the tonal plan, the sound of different modes and intonation complexes, and with the help of various textural presentation and skillful manipulation of the piece’s form, the author managed to transform the musical theme and saturate it with new experiences; on the basis of a generous piece, an elaborate pantype composition with an active dramaturgy, which has signs of a three-part structure, was masterfully created. The archaic theme of generosity, which was taken as a basis, was able to go from a monodic presentation to a colorful large-scale embodiment, from chamber sound to orchestral. Thanks to the means of polyphony, harmony, and orchestration, the composer managed to modernize the ancient genre of schedrivka while preserving elements of the symbolism of the ancient slavs: bourdon as a connection with the surrounding environment and as a way of spiritual communication with God; the variable tonal sounding of the two main themes only in the major represents revival and new life; the embodiment of the main theme in different octaves corresponds to various elements. Embodying Ukrainian folklore elements, Valerii Ivko successfully combined original ancient melodies with the help of his author’s style.